An Overview Onsustained Release Formulations Using Solid Dispersion as Solubility Enhancement Technique. - Nikita, Bhosale; Atish, Velhal; Vivek Kumar, Redasani; Poonam, Raut; Joshi, Varda (Asian Journal of Pharmaceutical Research and Development, 2023)
Biopharmaceutical classification system is important for determining the bioavailability of the drug. Drugs that dissolve slowly in water can be effectively solid-dispersed to increase their bioavailability. The bioavailability issue can be due to insufficient solubility of permeability. The poorly water-soluble medication dissolves more quickly when combined with the water-soluble carriers used to make solid dispersion. The review paper concentrates on the preparation techniques, benefits, drawbacks, and characterization of solid dispersion. Pharmaceuticals with sustained release have recently emerged as a very practical tool in medical practise, providing patients with a variety of real and perceived benefits. By minimising fluctuations in Using the therapeutic dose of the medicine in the body, sustained release is another promising reduction technique side effects. The major methods for creating tablets with a sustained release matrix are wet granulation, direct compression, or dispersion. In this review paper got the information about various polymers and different methods which are used for the formulate the sustained release tablet.